(untitled) (Salud, Arte y Cuidado, 2023)
Sexual conduct is one of the behaviors most strictly regulated by the different social groups and where transgressions of established norms have been punished with greater rigor. Condemned sexual interests change often. There are conditions that were accepted as normal in the past, but are now classified as mental disorders, such is the case of the Paraphilias. Paraphilias are considered forms of erotic behavior where the methods by which sexual arousal is achieved have a bonding structure in which the interpersonal component of the bond is not present or is present in a very unbalanced way. Such concerns or problems can cause and perpetuate other disorders in the person, the family, the community and the population in general and, therefore, affect the general health of the person, the family and society, since their existence can indicate the presence of other mental health problems. This review is proposed with the objective of analyzing the Paraphilias, since worldwide it has become a paradigm. The methodology used was a systematic review of documents published in journals, research papers and statistical data at a national and global level, publications and articles in manuals established by PAHO/WHO/UNICEF and APS.